Case study: description of the total quality system in a cold steel rolling unit (Research, Society and Development, 2019)
The main propose of this paper is to show using the case study method to explain how the total quality system was used in the cold rolling mill of a steel industry in Brazil. Conclusions and consequences of this work may be through the implementation of the total quality system, the technical capabilities were optimized, resulting in a lower cost of production, less investment with the maximum productive capacity of each equipment and production lines, in an Ideal Cost. With this Ideal Cost, we expect a greater production volume coupled with the excellence in the quality of the cold rolled product of the steel industry.